Influence of Key Threats on the National Security Assessment of the Republic of Poland - Stroyev, Andriy (Social Development and Security, 2025)
Purpose: to identify and characterize key threats to the Republic of Poland’s national security and analyze how these threats have influenced the assessment of the country’s national security, and the priorities set in its security strategy. Method: Analysis of official documents and expert studies on the subject of Poland’s national security. Findings: Key threats to the national security of the Republic of Poland (Russia’s neo-imperial policy, regional conflicts, migration pressure, energy dependence, new threats) were identified and their impact on the assessment of the country’s national security status and the determination of priorities for its security strategy was analyzed. Theoretical implications: The logic of forming the priorities of Poland’s security policy is revealed. Practical implications: The research can be used for a comparative analysis of approaches to national security of other countries, including Ukraine. Value: Clarifying the relationship between modern security challenges and the content of strategic decisions of the Polish leadership in the field of national security. Paper type: theoretical.